Holomorphic differentials of certain solvable covers of the projective line over a perfect field. Issue 13 (24th May 2018) - Marques, Sophie; Ward, Kenneth
Abstract: We provide a Boseck‐type basis of the space of holomorphic differentials for a large class of solvable covers of the projective line with perfect field of constants of characteristic p > 0 . Within this class, we also describe the Galois module structure of holomorphic differentials for abelian covers.